Strategi Peningkatan Infrastruktur Desa untuk Mendorong Perekonomian di Desa Limau Manis Kecamatan Tanjung Morawa - Mayora Mayora; Ahmad Suja'i Tanjung; Anita Khairani Siregar; Rehulina Rehulina; Arini Alfa Hidayah; Rofiil Harahap (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Limau Manis Village, Tanjung Morawa District, requires infrastructure development strategies to boost its economy. This research aims to identify effective strategies for enhancing village infrastructure and promoting economic growth. The findings indicate that infrastructure improvements, such as road construction, irrigation systems, and public facilities, can increase economic activity and community welfare. Therefore, effective infrastructure planning and management are essential for promoting economic development in Limau Manis Village.